The enthalpy changes for hydrogenation/dehydrogenation of Mg-based alloys - Yan Zheng; Shenglan Yang; Bin Hu; Yangfan Lu; Yan Yang; Kai Tang; Qun Luo; Bin Liu; Qian Li; Fusheng Pan (Journal of Magnesium and Alloys)
Magnesium-based hydrogen storage materials are promising candidates for hydrogen storage due to their high storage density and environmentally friendly properties. However, the high dehydrogenation enthalpy change (approximately 75 kJ/mol H2) and high dehydrogenation temperature (573 K at 0.1 MPa) of MgH2, limits the engineering application of Mg/MgH2 as a hydrogen storage material. This work reviews the prediction models and methods of enthalpy changes for hydriding/dehydriding (H/D) reactions in order to find out the ideas and ways to reduce them. The mechanism behind the improvement methods mainly includes two aspects, weakening Mg-H bond and compensating heat of reaction. Proceed from this, the experimental methods and enthalpy data as well as calculated values of enthalpy changes were compared systematically. Elements such as Ti, Nb, V, etc., with a small electronegativity difference compared to Mg, can reduce the hydrogenation and dehydrogenation enthalpy changes by forming strong Metal-H or Metal-Mg bonds. In addition, this review concludes with an outlook on the remaining challenge issues and prospects.